LA PREVALENCE DES NAUSEES ET VOMISSEMENTS CHIMIO-INDUITS - HARIA FATIMA ZAHRAA (My University, 2023)
Prevalence of chemotherapy-induced nausea and vomiting Prospective study at Kasr El Hiran hospital in Laghouat Objective: To study the prevalence of chemotherapy-induced nausea and vomiting (CINV), determine if the prescriptions in our department comply with the recommendations of expert societies, and evaluate the influence of certain patient-specific factors on the occurrence of CINV. Materials and Methods: This is a prospective observational study conducted at the day hospital of the medical oncology service at EPH Kasr El Hiran Laghouat, spanning a period of 3 months from September 21 to December 21, 2022. Results: At the end of this study, 50 women and 18 men were interviewed, with a mean age of 49.40 years. Breast cancer was the most frequent underlying neoplastic pathology (50%). The majority of chemotherapy protocols used were classified as low emetic risk (44.11%). The prevalence of CINV was 79%, of which 51.9% occurred in the delayed phase. According to our results, none of the risk factors appear to have an influence on the prevalence of CINV, and the prescriptions are not in compliance with the recommendations of expert societies. Conclusion: Our results indicate that the management of CINV remains overall unsatisfactory and could be improved by providing increased accessibility to aprepitant.
(DANS LE SERVICE D’ONCOLOGIE de l’EPH DE KASR EL-HIRENE
91 p.